Papakem Baduy: Sustainable Marketing Architecture and Socio-Ecological Resilience in the Midst of the Current of Modernity - Wuryandari, Nur Endah Retno; Purwanto, Setiyo; Damayanti, Ida Royani (Jurnal Ilmiah Global Education, 2025)
The Baduy indigenous people in Banten show a unique paradox: despite isolating themselves from modernity, they have strong socio-ecological resilience and economic adaptation. This ethnographic research aims to uncover their resilience architecture and sustainable marketing model rooted in the Papakem or Pikukuh philosophy of life. Data were collected through participatory observations, interviews with traditional stakeholders, artisans, and the younger generation of Baduy Luar, as well as literature studies, and then analyzed thematically. As a result, Baduy resilience is a conscious system supported by: (1) leuit as a food security institution, and (2) huma as an ecological risk mitigation strategy. The study also found that the marketing transformation of tourism interactions towards the adoption of digital technology by the Baduy Luar reflects symbolic capitalism. Papakem acts as an operating system that maintains conservation ethics while allowing economic involvement without abandoning cultural identity.